Within-lesion heterogeneity of subcortical DWI lesion evolution, and stroke outcome: A voxel-based analysis. Issue 7 (July 2020) - Duering, Marco; Adam, Ruth; Wollenweber, Frank A; Bayer-Karpinska, Anna; Baykara, Ebru; Cubillos-Pinilla, Leidy Y; Gesierich, Benno; Araque Caballero, Miguel Á; Stoecklein, Sophia; Ewers, Michael; Pasternak, Ofer; Dichgans, Martin
The fate of subcortical diffusion-weighted imaging (DWI) lesions in stroke patients is highly variable, ranging from complete tissue loss to no visible lesion on follow-up. Little is known about within-lesion heterogeneity and its relevance for stroke outcome. Patients with subcortical stroke and recruited through the prospective DEDEMAS study (NCT01334749) were examined at baseline ( n  = 45), six months ( n  = 45), and three years ( n  = 28) post-stroke. We performed high-resolution structural MRI including DWI. Tissue fate was determined voxel-wise using fully automated tissue segmentation. Within-lesion heterogeneity at baseline was assessed by free water diffusion imaging measures. The majority of DWI lesions (66%) showed cavitation on six months follow-up but the proportion of tissue turning into a cavity was small (9 ± 13.5% of the DWI lesion). On average, 69 ± 25% of the initial lesion resolved without any visually apparent signal abnormality. The extent of cavitation at six months post-stroke was independently associated with clinical outcome, i.e. modified Rankin scale score at six months (OR = 4.71, p  = 0.005). DWI lesion size and the free water-corrected tissue mean diffusivity at baseline independently predicted cavitation. In conclusion, the proportion of cavitating tissue is typically small, but relevant for clinical outcome. Within-lesion heterogeneity at baseline on advanced diffusion imaging is predictive of tissue fate.